Necrotizing fasciitis following a monkey bite - Jayabal Pandiaraja (Apollo Medicine)
Necrotizing fasciitis (NF) is rapidly spreading bacterial infection of a facial plane. It has a higher mortality rate in patients with diabetes and immunocompromised state. The initial presentation mimics cellulitis and most of the cases are misdiagnosed. Delayed diagnosis and treatment increase mortality by nearly 100%. Our case developed NF with septic shock following a monkey bite. The patient underwent prompt fasciotomy along with extensive wound debridement. Later, the patient underwent secondary suturing with a skin graft for wound cover. NF following money bite is not reported in the literature till now. Hence, early diagnosis and prompt surgical debridement in monkey bites will reduce the incidence of mortality due to NF.